2009
DOI: 10.1007/s10640-009-9267-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contingent Valuation to Elicit Willingness-to-Pay for the Benefits of Developmental Health Risk Reductions

Abstract: Contingent valuation, Developmental effects, IQ, PCBs, QALY, Risk assessment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Halkos and Matsiori [117] also reported that, as the level of income increases, people would be more willing to pay. Others studies using meta-analysis data had similar findings [129].…”
Section: Discussionmentioning
confidence: 60%
“…Halkos and Matsiori [117] also reported that, as the level of income increases, people would be more willing to pay. Others studies using meta-analysis data had similar findings [129].…”
Section: Discussionmentioning
confidence: 60%
“…One category of bads is environmental damage (Carson et al, 2003; Loureiro et al, 2009; von Stackelberg and Hammitt, 2009; Martin-Ortega et al, 2011). Another category includes a public good that benefits society but harms a host location, such as locating a prison or a toxic waste dump.…”
Section: Introductionmentioning
confidence: 99%
“…For a similar good, VonStackelberg and Hammitt (2009) used stated-preference methods to estimate parents' WTP to prevent a delay in reading attainment or an IQ deficit in their children associated with exposure to particular chemicals (PCBs) in the environment. Their findings suggest that WTP is small compared with estimates of the effect of lower IQ on lifetime earnings.…”
mentioning
confidence: 99%